2020
DOI: 10.1007/978-3-319-71058-7_7-1
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and the Sustainable Development Goals (SDGs)

Abstract: Corporate Social Responsibility is the voluntary act of companies to integrate social and environmental interests into their business approaches, to contribute to sustainable development and to be accountable for their impact on the environment and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…This provides new tradeoffs, but examples from this research showed that those are not necessarily balanced, which strengthens the call for holistic and critical approaches with regard to the TBL [1,15,54]. For example, the results show that, under influence of international ethical standards, a focus on the social bottom line is a "need to have" in order to prevent social misconduct.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This provides new tradeoffs, but examples from this research showed that those are not necessarily balanced, which strengthens the call for holistic and critical approaches with regard to the TBL [1,15,54]. For example, the results show that, under influence of international ethical standards, a focus on the social bottom line is a "need to have" in order to prevent social misconduct.…”
Section: Discussionsupporting
confidence: 51%
“…"Corporate Social Responsibility is the voluntary act of companies to integrate social and environmental interests into their business approaches, to contribute to sustainable development and to be accountable for their impact on the environment and society" [54].…”
Section: Corporate Social Responsibility (Csr)mentioning
confidence: 99%
“…Diminishing government support encourages entrepreneurs to tackle emerging societal problems in an innovative and sustainable manner (Dwivedi and Weerawardena, 2018;Lubberink, 2020 the literature date back to the late 1960s and include the Ashoka Foundation, which was started in India, providing seed capital to entrepreneurs with a social vision; and the Grameen Bank, which was established to fight poverty in Bangladesh (Mair and Martí, 2006). However, social entrepreneurship predates to the 20th century (Molderez, 2020). New Lanark Mills is often seen as the first example of social entrepreneurship (Shaw and Carter, 2007).…”
Section: Introductionmentioning
confidence: 99%